School-Based Management in Efforts to Develop Student Life Skills in Community - Wahyudi, Apri; Mantik, Aliyah; Windayanti, Wiwin; Muhtarom, Muhtarom; Kusuma, Nurhadi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This study uses a qualitative approach. The technique of taking data sources in this study is using Snow Bolling Sampling. The data collection procedures used are observation, review, and documentation studies. In conducting this data analysis, the author uses several methods, namely the induction, deduction, and comparison methods. School-based management at SMP Islam Terpadu Insan Madani Boarding School strongly supports the effectiveness of efforts to develop students' life skills. This is done by integrating general life skills in each subject so that every teaching and learning activity aims to develop certain life skills. Second, organizing a "Student Day" program consisting of 10 types of activities, and students are free to choose one or more of them that best suit their interests and talents. Third, increasing community participation is done by involving them in planning, implementing, supervising, and evaluating school programs. And fourth, creating a conducive school culture can be seen from the habits that continue to be carried out in daily associations and the implementation of the school's vision which is the motto for all school residents.